2010
DOI: 10.1007/s00270-010-0045-2
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Poly-l-Lactic Acid Biodegradable Stents in Normal Canine Bile Ducts

Abstract: Our results suggest that PLLA bioabsorbable stents seems to be useful for implantation in the biliary system with further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 13 publications
0
19
0
3
Order By: Relevance
“…If the stent was patent up to 6 months after insertion, the authors described endothelial proliferation or embedding of the stent in 75% of the cases. Moreover, stent fragmentation was seen in all stents retrieved at the end of the study (9 months) [75].…”
Section: Bioabsorbable Stentsmentioning
confidence: 98%
“…If the stent was patent up to 6 months after insertion, the authors described endothelial proliferation or embedding of the stent in 75% of the cases. Moreover, stent fragmentation was seen in all stents retrieved at the end of the study (9 months) [75].…”
Section: Bioabsorbable Stentsmentioning
confidence: 98%
“…Bioabsorbable stent is still in laboratory stages, without clinical use so far 39-42. It is noteworthy that recently a research team in Finland has gained an unparalleled position in this field when they reported the results of a phase 1 clinical study after long and hard work in animal tests 43…”
Section: Studies For Functional Stentmentioning
confidence: 99%
“…No gross degradation was seen at 1, 3, or 6 months, but fragmentation had started at 9 months when the stents were removed. 31 Haber et al demonstrated safe deployment of a 10 mm674 mm bioabsorbable poly-L-lactide stent in 48 of 50 patients with malignant biliary obstruction. 32 Notably, radial compliance force was reduced by 60% in this stent relative to plastic stents.…”
Section: Bioabsorbable Stentsmentioning
confidence: 99%
“…Yamamoto et al investigated a biodegradable 6 mm615 mm poly-L-lactic acid Z pattern stent with platinum markers and placed them in 12 dogs. 31 Cholangiography and laparotomy were performed at 1, 3, 6, and 9 months, and the stents remained patent throughout. Endothelial ingrowth into the wall was seen in nine of 12 dogs.…”
Section: Bioabsorbable Stentsmentioning
confidence: 99%